Nutritional Vulnerability in Early Stages of the Freshwater Ornamental "Red Cherry Shrimp" Neocaridina Davidi () (Caridea: Atyidae). Issue 5 (1st September 2015) - Pantaleão, João Alberto Farinelli; Barros-Alves, Samara de P.; Tropea, Carolina; Alves, Douglas F. R.; Negreiros-Fransozo, Maria Lucia; López-Greco, Laura S.
Abstract: This study evaluated the starvation resistance of the shrimp Neocaridina davidi during the first and the third juvenile stages (named here as JI and JIII) by means of the estimation of point-of-no-return (PNR_50) . Two experiments were conducted with increasing numbers of days without food and two controls (one with continuous feeding, CF; the other, with continuous starvation, CS). Time to the first molt and number of molts did not differ among the treatments beginning at JI or JIII. Nevertheless, longer periods of starvation influenced growth and survival of juveniles beginning the starvation as JI, but these effects were not observed in JIII. The estimated values of PNR_50 for JI and JIII were 16.15 ± 0.31 and 9.44 ± 0.26 days, respectively. The early stages of the life cycle are more tolerant to starvation than other decapods previously studied. Such ability indicates a great potential of this species for aquaculture.